Malaria in Guinean Rural Areas: Prevalence, Management, and Ethnotherapeutic Investigations in Dionfo, Sub-Prefecture of Labe - Baldé, Aliou Mamadou; Balde, Alpha Oumar; Bah, Bilo; Barry, Halimatou; Traore, Saidou; Bah, Fatoumata; Balde, Mamadou Aliou; Camara, Aissata; Traore, Mohamed Sahar; Balde, Elhadj Saidou; Sylla, Ibrahima Kalil; Diallo, Sadou (Planta Medica, 2021)
As part of a validation program of antimalarial traditional recipes, an ethnotherapeutic approach was applied in Dionfo, a meso-endemic Guinean rural area where conventional health facilities are insufficient. A prevalence investigation indicated a malarial burden of 4.26%. Ethnomedical and ethnobotanical surveys led to a collection of 63 plant species used against malaria from which Terminalia albida (Combretaceae) was one of the most cited. Ethnotherapeutic evaluation of a remedy based on T. albida was applied to 9 voluntary patients suffering from uncomplicated malaria. Treatment of 7 to 14 days led to an improvement of clinical symptoms and a complete parasite clearance achievement of 8/9 patients without side effects. In addition to antiplasmodial activity in vitro and in vivo previously described, this study indicates an efficacy to support the antimalarial traditional use of T. albida, which could constitute a first-aid treatment when access to other medicines is delayed in the Dionfo community. Ethnotherapeutical investigation could be a valuable approach to guide subsequent investigations on traditional remedies.
Keywords: malaria; Guinea; rural areas; ethnotherapeutic; Terminalia albida